RUANG LINGKUP ADMINISTRASI PENDIDIKAN - Metti Fathimah; Hanik Rahmawati Solikhah; Anny Izzatul Mujahidah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Educational administration is a crucial component in the implementation of education, as it functions to coordinate all resources to achieve educational goals effectively and efficiently. In practice, educational administration is not limited to clerical activities but encompasses planning, organizing, implementing, supervising, and evaluating all educational components. This article aims to comprehensively examine the scope of educational administration within the context of the Indonesian education system. The research method employed is a literature study by reviewing various scholarly sources relevant to educational administration and management. The findings indicate that the scope of educational administration includes curriculum administration, student administration, administration of educators and educational staff, facilities and infrastructure management, financial administration, school, community relations, and general administrative services. A comprehensive understanding of the scope of educational administration is expected to serve as a foundation for improving the quality of educational institution management in a sustainable manner.